Maderas gimnospérmicas de la Formación Carapacha (Pérmico), provincia de La Pampa, Argentina - Crisafulli, Alexandra María Cristina (2000)
This paper describes four gyrnnosperms woods from the fluvial-Iacustrine Carapacha Formation (Early Perrnian to early Late Permian) of La Pampa, Argentina. All the material was preserved as driftwood in sandstone channel facies (mineralized by carbonates or silica) and associated with a G/ossopteris flora. One specimen is referred to Sdicfiicaulia peripaiudica Mussa on account of the anatomical characters of the pith, and primary and secondary xylem. Only secondary xylem is present in the remaining woods and therefore they are assigned to three Araucarioxvlon species: A. allanii (Krausel) Maheshwari, A. kharhariense (Maithy) Maheshwari and A. iamndtuense (Maithy) Maheshwari. In the analyzed material there is anatomical evidence of humidity shortage during the life of these plants, which is in agreement with the sedimentologic interpretation of the sedimentary sequence. These species were also recorded in the Permian of Brazil, Antarctica, and India.